Příprava a studium série polymerů na bázi diketopyrrolopyrrolů (DPP) jako fotoaktivních látek - Solanský, Lukáš (Vysoké učení technické v Brně. Fakulta chemická, 2024)
Předkládaná diplomová práce pojednává o polymerech na bázi organických pigmentů, jejich přípravě, charakterizacích a využití jakožto fotoaktivních látek se zaměřením na umělou fotosyntézu. Experimentální části je věnovaná přípravě polymerů na bázi diketopyrrolopyrrolů (DPP). Bylo připraveno 7 DPP derivátů s 5 různými postranními řetězci. Byly porovnány přípravy DPP polymerů pomocí Stilleovy reakce a přímé arylace. Díky vyšší efektivitě a nižší náročnosti přímé arylace byla tato metoda polymerace využita na přípravu série 20 polymerů složená z kombinace 5 DPP derivátů a 4 komonomerů. U syntézy několika výsledných polymerů byl pozorován vznik nerozpustného podílu, který nebylo možné dostupnými metodami charakterizovat, a i následná aplikace takových materiálů není díky tomu umožněna. Na základě získaných dat se ukázalo, že zejména objemná skupina adamantanu a komonomer tetrafluorbenzen nejsou pro přípravu polymerů vhodné, jelikož vedly k velmi omezeně rozpustným materiálům, který měly navíc nízký stupeň polymerace. Naopak polymery obsahující butyl-TEG, oktadekan, komonomer thiofen a částečně i benzothiadiazol měly stupeň polymerace v rozmezí 10-33 a vykazovaly skvělé spektrální i optoelektrické vlastnosti. Testy fotokatalytického vývoje vodíku za pomocí DPP polymerů jsou ve vývoji, ale v prvotních měřeních na vybraných materiálech polymerů (P14 a P20) vodík nebyl prokazatelně detekován.

The present diploma thesis deals with polymers based on organic pigments, their preparation, characterization and use as photoactive substances with a focus on artificial photosynthesis. The experimental part is devoted to the preparation of diketopyrrolopyrrole (DPP) based polymers. 7 DPP derivatives with 5 different side chains were prepared. The preparation of DPP polymers by Stille cross-coupling reaction and direct arylation were compared. Due to the higher efficiency and lower complexity of direct arylation, this polymerization method was used to prepare a series of 20 polymers consisting of a combination of 5 DPP derivatives and 4 comonomers. In the synthesis of several of the resulting polymers, the formation of an insoluble moiety was observed which could not be characterized by available methods, and even the subsequent application of such materials is not possible due to this. On the basis of the data obtained, it became apparent that in particular the bulky adamantane group and the comonomer tetrafluorobenzene were not suitable for the preparation of polymers, as they resulted in very limited soluble materials which, moreover, had a low degree of polymerization. In contrast, polymers containing butyl-TEG, octadecane, the comonomer thiophene and partially benzothiadiazole had degrees of polymerization in the range of 10-33 and exhibited excellent spectral and optoelectric properties. Tests of photocatalytic hydrogen evolution using DPP polymers are under development, but hydrogen was not demonstrably detected in initial measurements on selected polymer materials (P14 and P20).
Preparation and study of a series of diketopyrrolopyrrole (DPP)-based polymers as photoactive substances
Keywords: Organické pigmenty; Diketopyrrolopyrroly (DPP); Příprava polymerů; Přímá arylace; Umělá fotosyntéza; Vývoj vodíku; Organic pigments; Diketopyrrolopyrroles (DPP); Polymer preparation; Direct arylation; Artificial photosynthesis; Hydrogen evolution